Testing water banking recovery policies to secure drought water supply in semi-arid areas with a changing climate - Peter Dillon; Bridget R. Scanlon; Rebecca Bernat; Dennis Gonzalez; Constantin Seidl; Declan Page; Rebecca Doble; John Radcliffe; Adam Hutchinson; Sharon B. Megdal (Groundwater for Sustainable Development, 2026)

Probabilistic storm surge and flood-inundation modeling of the Texas gulf coast using super-fast INundation of CoastS (SFINCS) - Wonhyun Lee; Alexander Y. Sun; Bridget R. Scanlon (Coastal Engineering, 2025)

Evaluation of the Anti-Inflammatory Effects of Novel Fatty Acid-Binding Protein 4 Inhibitors in Microglia - Yi Ling Low; Ethan Kreutzer; Indu R. Chandrashekaran; Luke A. Adams; Jason Pun; Bradley C. Doak; Yijun Pan; Jennifer L. Short; Martin J. Scanlon; Joseph A. Nicolazzo (Journal of Neuroimmune Pharmacology, 2025)
Fatty acid-binding protein 4 (FABP4) is a key lipid binding protein expressed in microglia, which has been demonstrated to play a critical role in microglial-mediated neuroinflammation, a component of many neurodegenerative diseases. Compounds able to inhibit the function of FABP4 have shown promise in reducing microglial-mediated neuroinflammation, however, their physicochemical properties would prevent their ability to be easily formulated and traverse the blood–brain barrier (BBB) in order to access microglial FABP4. To this end, this study assessed the ability of a series of FABP4 inhibitors, with more desirable physicochemical properties, to attenuate microglial inflammation in an in vitro setting. Four inhibitors with varying affinity to FABP4, as measured by isothermal titration calorimetry (MFP-0011462, MFP-0012314, MFP-0012318, and MFP-0012328), were assessed for their ability to induce toxicity and attenuate reactive oxygen species (ROS) generation and tumour necrosis factor-α (TNF-α) release from lipopolysaccharide (LPS)-activated BV-2 microglia. All FABP4 inhibitors were determined to be soluble in the aqueous buffers at the highest concentration used in the assays (100 µM). Isothermal titration calorimetry demonstrated that the compounds had varying affinities for FABP4 (K D values of 316 nM to > 100 µM). The ability of FABP4 inhibitors to reduce LPS-mediated ROS production aligned with their K D for FABP4, with the most effective inhibitor (MFP-0012328) also able to reduce TNF-α production (by RT-qPCR) and TNF-α release from LPS-activated BV-2 cells by 17% and 25%, respectively. These studies have demonstrated that a series of FABP4 inhibitors with more appropriate physicochemical properties for BBB penetration are able to reduce microglial-mediated inflammation, which may be of benefit in diseases where overactivation of microglia leads to neurodegeneration.

Shifting agricultural land use and its unintended water consumption in the North China Plain - Liang Dong; Di Long; Caijin Zhang; Yingjie Cui; Yanhong Cui; Yiming Wang; Luoqi Li; Zhongkun Hong; Ling Yao; Jinling Quan; Liangliang Bai; Hao Wang; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Controls on lithium content of oilfield waters in Texas and neighboring states (USA) - Roxana Darvari; Jean-Philippe Nicot; Bridget R. Scanlon; J. Richard Kyle; Brent A. Elliott; Kristine Uhlman (Journal of Geochemical Exploration, 2024)

Hindcasting compound pluvial, fluvial and coastal flooding during Hurricane Harvey (2017) using Delft3D-FM - Wonhyun Lee; Alexander Y. Sun; Bridget R. Scanlon; Clint Dawson (Natural Hazards, 2024)

GEMAS: Chemical weathering of silicate parent materials revealed by agricultural soil of Europe - Philippe Négrel; Anna Ladenberger; Clemens Reimann; Alecos Demetriades; Manfred Birke; Martiya Sadeghi; S. Albanese; M. Andersson; R. Baritz; M.J. Batista; A. Bel-lan; D. Cicchella; et al. (Chemical Geology, 2023)

Distribution of rare earth and other critical elements in lignites from the Eocene Jackson Group, Texas - James C. Hower; Peter D. Warwick; Bridget R. Scanlon; Robert C. Reedy; Tristan M. Childress (International Journal of Coal Geology, 2023)

Evaluating effectiveness of girdle-herbicide containment of below-ground spread of oak wilt (Bretziella fagacearum) - Dustin R. Bronson; Jed Meunier; Teresa R. Pearson; Kyoko Scanlon (Forest Ecology and Management, 2023)

New improved Brazilian daily weather gridded data (1961–2020) - Alexandre C. Xavier; Bridget R. Scanlon; Carey W. King; Aline I. Alves (International Journal of Climatology, 2022)
The demand for meteorological gridded datasets has increased within the last few years to inform studies such those in climate, weather, and agriculture. These studies require those data to be readily usable in standard formats with continuous spatial and temporal coverage. Since 2016, Brazil has a daily gridded meteorological data set with spatial resolution of 0.25° × 0.25° from January 1, 1980 to December 31, 2013 which was well received by the community. The main objective of this work is to improve the Brazilian meteorological data set. We do this by increasing the resolution of the minimum and maximum temperature (Tmax and Tmin) gridded interpolations from 0.25° × 0.25° to 0.1° × 0.1° by incorporating data on topographic relief, and increasing the time period covered (January 1, 1961–July 31, 2020). Besides Tmax and Tmin, we also gridded precipitation (pr), solar radiation (Rs), wind speed (u2), and relative humidity (RH) using observed data from 11,473 rain gauges and 1,252 weather stations. By means of ranked cross‐validation statistics, we selected the best interpolation among inverse distance weighting and angular distance weighting methods. We determined that interpolations for Tmax and Tmin are improved by using the elevation of a query point, that accounts for topographic relief, and a temperature lapse rate. Even though this new version has ≈25 years more data relative to the previous one, statistics from cross‐validation were similar. To allow researchers to assess the performance of the interpolation relative to station data in the area, we provide two types of gridded controls.

Beyond species counts for assessing, valuing, and conserving biodiversity: response to Wallach et al. 2019 - Ninon F. V. Meyer; Niko Balkenhol; Trishna Dutta; Maarten Hofman; Jean‐Yves Meyer; Euan G. Ritchie; Charlotte Alley; Chad Beranek; Cassandra K. Bugir; Alex Callen; Simon Clulow; Michael V. Cove; et al. (Conservation Biology, 2021)
Article impact statement : Combining native and non‐native species to evaluate biodiversity is overly simplistic and may undermine the conservation of ecosystems.

Evaluating Regeneration in Heterobasidion Root Disease Infested Stands in the Lake States - Michael C Demchik; Monique L Sakalidis; Michael Hillstrom; Kyoko Scanlon; Trevor A Adams; Katherine R Minnix (Forest Science, 2020)
Heterobasidion root disease (HRD) infection is becoming increasingly common in red pine plantations of the Lake States. Although stump treatment can reduce rates of overland transmission, infested stands continue to experience expansion of mortality pockets. Natural regeneration into HRD mortality pockets can assist with revegetation. The objective of this study was to determine what tree species naturally regenerate in red pine plantations impacted by HRD in Wisconsin and Michigan. We visited 49 pockets (in 31 stands) in Wisconsin and Michigan that had existing confirmed HRD infections during the fall of 2017. We surveyed the regeneration in the pocket and measured the species and basal area of overstory trees 10 m from the expanding edge of the pocket. Overall, pockets were regenerating with desirable species, some of which are susceptible to HRD. Additionally, woody invasive species were present in 39 percent of the pockets. We expect these pockets to generally fill with desirable species of regeneration, although long-term successful regeneration by susceptible species such as pines may be limited.

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Topical Collection: Determining groundwater sustainability from long-term piezometry in Sub-Saharan Africa - Richard G. Taylor; Guillaume Favreau; Bridget R. Scanlon; Karen G. Villholth (Hydrogeology Journal, 2019)

Sixty years of global progress in managed aquifer recharge - P. Dillon; P. Stuyfzand; T. Grischek; M. Lluria; R. D. G. Pyne; R. C. Jain; J. Bear; J. Schwarz; W. Wang; E. Fernandez; C. Stefan; M. Pettenati; et al. (Hydrogeology Journal, 2019)

Fingerprinting groundwater salinity sources in the Gulf Coast Aquifer System, USA - Ali H. Chowdhury; Bridget R. Scanlon; Robert C. Reedy; Steve Young (Hydrogeology Journal, 2018)

What caused the spring intensification and winter demise of the 2011 drought over Texas? - D. Nelun Fernando; Kingtse C. Mo; Rong Fu; Bing Pu; Adam Bowerman; Bridget R. Scanlon; Ruben S. Solis; Lei Yin; Robert E. Mace; John R. Mioduszewski; Tong Ren; Kai Zhang (Climate Dynamics, 2016)

Erratum to: Groundwater Storage Changes: Present Status from GRACE Observations - Jianli Chen; James S. Famiglietti; Bridget R. Scanlon; Matthew Rodell (Surveys in Geophysics, 2016)

Daily gridded meteorological variables in Brazil (1980–2013) - Alexandre C. Xavier; Carey W. King; Bridget R. Scanlon (International Journal of Climatology, 2016)
Basic meteorological data are essential for evaluating impacts of spatiotemporal variability in climate forcing on hydrology and agroecosystems. The objective of this work was to develop high‐resolution grids (0.25 ∘ × 0.25 ∘ ) of daily precipitation, evapotranspiration, and the five climate variables generally required to estimate evapostranspiration for Brazil. These five variables are maximum and minimum temperature, solar radiation, relative humidity, and wind speed. We tested six different interpolation schemes to create the grids for these variables. The data were obtained from 3625 rain gauge and 735 weather stations for period of 1980–2013. We used a cross‐validation approach that compares point observed data to point interpolated estimates to select the best interpolation scheme for each climate variable. We also present the performance of the best interpolation for each climate variable at daily timescales and for river basins. The inverse distance weighting and angular distance weighting methods produced the best results. Performance of all methods was poorer prior to 1995 because of fewer stations and available data. The performance of the interpolation varies for different seasons for almost all variables. Forecasting capability was tested for precipitation only and performed adequately for the system state (wet or dry). Variations in the interpolation schemes across river basins are primarily attributed to differences in gauge or station network density. This freely available gridded meteorological data set significantly advances the availability of climate data in Brazil.

Groundwater Storage Changes: Present Status from GRACE Observations - Jianli Chen; James S. Famigliett; Bridget R. Scanlon; Matthew Rodell (Surveys in Geophysics, 2016)

Long-term increase in diffuse groundwater recharge following expansion of rainfed cultivation in the Sahel, West Africa - Maïmouna Ibrahim; Guillaume Favreau; Bridget R. Scanlon; Jean Luc Seidel; Mathieu Le Coz; Jérôme Demarty; Bernard Cappelaere (Hydrogeology Journal, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

The Dublin SURGE Project: geochemical baseline for heavy metals in topsoils and spatial correlation with historical industry in Dublin, Ireland - M. M. Glennon; P. Harris; R. T. Ottesen; R. P. Scanlon; P. J. O’Connor (Environmental Geochemistry and Health, 2014)
The Dublin SURGE (Soil Urban Geochemistry) Project is Dublin’s first baseline survey of heavy metals and persistent organic pollutants in topsoils and is part of a Europe-wide initiative to map urban geochemical baselines in ten cities. 1,058 samples were collected as part of a stratified random sampling programme in the greater Dublin area to give an overview of baseline conditions in the city. Samples were analysed for 31 inorganic elements including heavy metals. Analysis of results indicates that the concentrations of lead, copper, zinc and mercury are strongly influenced by human activities, with elevated concentrations in the city docklands, inner city and heavy industry areas. Sources of heavy metals in these areas may include historical industry, coal burning, re-use of contaminated soil, modern traffic and leaded paint and petrol. Concentrations of other inorganic elements in topsoil show patterns which are strongly related to regional bedrock parent material. The spatial distributions of heavy metals, in particular Pb and As, are explored in detail with respect to regional geology and the influence of historical industry on soil quality. Exploratory data, geostatistical and correlation analyses suggest that the concentrations of heavy metals tend to increase as the intensity of historical industrial activity increases. In particular, drinks production, power generation, oil/gas/coal, metals and textile historical industries appear to be the contamination source for several heavy metals. The data provide a geochemical baseline relevant to the protection of human health, compliance with environmental legislation, land use planning and urban regeneration.

Internal wave‐driven transport of fluid away from the boundary of a lake - Danielle J. Wain; Michael S. Kohn; Joshua A. Scanlon; Chris R. Rehmann (Limnology and Oceanography, 2013)
A field experiment was conducted to study transport of fluid from the boundary to the interior of a lake. Tracking of a tracer injected into the metalimnion was combined with measurements of meteorological forcing, internal waves, and temperature microstructure. Seiches of vertical mode 2 and horizontal modes 1 and 2 were initiated after a wind event, and the tracer moved 950 m into the interior after 29.2 h. Four potential mechanisms for spreading of the tracer from the boundary to the interior were considered: intrusions from boundary mixing, horizontal dispersion, advection by seiches, and advection and dispersion driven by internal waves. Some evidence of boundary mixing was observed 0.5 h before the dye injection, when the speed of seiche‐driven currents was large, but a model of an intrusion driven by steady input overpredicted the propagation distance by a factor of about two. A one‐dimensional model with only dispersion yielded a dispersion coefficient of 0.8 m 2 s −1 , and a one‐dimensional model with only advection caused by internal waves predicted the position of the peak concentration and a change in longitudinal variance that was 60% of the measured change. Estimates of dispersion caused by the interaction of vertical diffusion with velocity gradients in the internal wave field are large enough to explain the rest of the spreading and suggest that the transport can be modeled as wave‐driven advection and dispersion.

Sources of groundwater pumpage in a layered aquifer system in the Upper Gulf Coastal Plain, USA - Yun Huang; Bridget R. Scanlon; Jean-Philippe Nicot; Robert C. Reedy; Alan R. Dutton; Van A. Kelley; Neil E. Deeds (Hydrogeology Journal, 2012)

Impacts of soil conservation on groundwater recharge in the semi-arid Loess Plateau, China - John B. Gates; Bridget R. Scanlon; Xingmin Mu; Lu Zhang (Hydrogeology Journal, 2011)

Groundwater recharge in natural dune systems and agricultural ecosystems in the Thar Desert region, Rajasthan, India - Bridget R. Scanlon; Abhijit Mukherjee; John Gates; Robert C. Reedy; Amarendra K. Sinha (Hydrogeology Journal, 2010)

Characterization of lipophilic drug binding to rat intestinal fatty acid binding protein - Tony Velkov; Maria L. R. Lim; James Horne; Jamie S. Simpson; Christopher J. H. Porter; Martin J. Scanlon (Molecular and Cellular Biochemistry, 2009)

Estimating groundwater recharge in a cold desert environment in northern China using chloride - John B. Gates; W. M. Edmunds; Jinzhu Ma; Bridget R. Scanlon (Hydrogeology Journal, 2008)

Factors affecting river health and its assessment over broad geographic ranges: The Western Australian experience - S. A. Halse; M. D. Scanlon; J. S. Cocking; M. J. Smith; W. R. Kay (Environmental Monitoring and Assessment, 2007)

Genetic variation at the growth hormone (GH1) and growth hormone receptor (GHR) loci as a risk factor for hypertension and stroke - Martin Horan; Vicky Newsway; Yasmin; Mark D. Lewis; Tammy E. Easter; D. Aled Rees; Arti Mahto; David S. Millar; Annie M. Procter; Maurice F. Scanlon; Ian B. Wilkinson; Ian P. Hall; et al. (Human Genetics, 2006)

Impact of land use and land cover change on groundwater recharge and quality in the southwestern US - Bridget R. Scanlon; Robert C. Reedy; David A. Stonestrom; David E. Prudic; Kevin F. Dennehy (Global Change Biology, 2005)
Humans have exerted large‐scale changes on the terrestrial biosphere, primarily through agriculture; however, the impacts of such changes on the hydrologic cycle are poorly understood. The purpose of this study was to test the hypothesis that the conversion of natural rangeland ecosystems to agricultural ecosystems impacts the subsurface portion of the hydrologic cycle by changing groundwater recharge and flushing salts to underlying aquifers. The hypothesis was examined through point and areal studies investigating the effects of land use/land cover (LU/LC) changes on groundwater recharge and solute transport in the Amargosa Desert (AD) in Nevada and in the High Plains (HP) in Texas, US. Studies use the fact that matric (pore‐water‐pressure) potential and environmental‐tracer profiles in thick unsaturated zones archive past changes in recharging fluxes. Results show that recharge is related to LU/LC as follows: discharge through evapotranspiration (i.e., no recharge; upward fluxes −1 ) in natural rangeland ecosystems (low matric potentials; high chloride and nitrate concentrations); moderate‐to‐high recharge in irrigated agricultural ecosystems (high matric potentials; low‐to‐moderate chloride and nitrate concentrations) (AD recharge: ∼130–640 mm yr −1 ); and moderate recharge in nonirrigated (dryland) agricultural ecosystems (high matric potentials; low chloride and nitrate concentrations, and increasing groundwater levels) (HP recharge: ∼9–32 mm yr −1 ). Replacement of rangeland with agriculture changed flow directions from upward (discharge) to downward (recharge). Recent replacement of rangeland with irrigated ecosystems was documented through downward displacement of chloride and nitrate fronts. Thick unsaturated zones contain a reservoir of salts that are readily mobilized under increased recharge related to LU/LC changes, potentially degrading groundwater quality. Sustainable land use requires quantitative knowledge of the linkages between ecosystem change, recharge, and groundwater quality.

Application of a quartz crystal microbalance to evaluate biodegradability of starch by Bacillus subtilis - M. Jenkins; M. Horsfall; D. Mathew; M. Scanlon; R. Jayasekara; G.T. Lonergan (Biotechnology Letters, 2004)

Did Canada geese or other birds spread Cylindrocladium Black Rot of peanuts? - R. B. Hiller; P. F. Scanlon (European Journal of Wildlife Research, 2002)

Choosing appropriate techniques for quantifying groundwater recharge - Bridget R. Scanlon; Richard W. Healy; Peter G. Cook (Hydrogeology Journal, 2002)

Theme issue on groundwater recharge - Bridget R. Scanlon; Peter G. Cook (Hydrogeology Journal, 2002)

Surface Water Transport of Lead at a Shooting Range - J. R. Craig; J. D. Rimstidt; C. A. Bonnaffon; T. K. Collins; P. F. Scanlon (Bulletin of Environmental Contamination and Toxicology, 1999)

Pathotyping isolates of Newcastle disease virus using antipeptide antibodies to pathotype-specific regions of their fusion and hemagglutinin-neuraminidase proteins - D. B. Scanlon; G. L. Corino; B. J. Shiell; A. J. Della-Porta; R. J. Manvell; D. J. Alexander; A. N. Hodder; J. J. Gorman (Archives of Virology, 1999)

Computerized video image analysis to quantify color of potato chips - M. G. Scanlon; R. Roller; G. Mazza; M. K. Pritchard (American Journal of Potato Research, 1994)